Injectable Hydrogel-Based Nanocomposites for Cardiovascular Diseases - Liao, Xiaoshan (Front Bioeng Biotechnol, 2020)
Cardiovascular diseases (CVDs), including a series of pathological disorders, severely affect millions of people all over the world. To address this issue, several potential therapies have been developed for treating CVDs, including injectable hydrogels as a minimally invasive method. However, the utilization of injectable hydrogel is a bit restricted recently owing to some limitations, such as transporting the therapeutic agent more accurately to the target site and prolonging their retention locally. This review focuses on the advances in injectable hydrogels for CVD, detailing the types of injectable hydrogels (natural or synthetic), especially that complexed with stem cells, cytokines, nano-chemical particles, exosomes, genetic material including DNA or RNA, etc. Moreover, we summarized the mainly prominent mechanism, based on which injectable hydrogel present excellent treating effect of cardiovascular repair. All in all, it is hopefully that injectable hydrogel-based nanocomposites would be a potential candidate through cardiac repair in CVDs treatment.